2020
DOI: 10.3389/fnbeh.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Drug Seeking Following Drug Taking in a Sexual Context Requires Anterior Cingulate Cortex Activity in Male Rats

Abstract: Individual variance in vulnerability to develop addictions is influenced by social factors. Specifically, drug-taking in a sexual context appears to enhance further drug-seeking behavior in human users, as these users identify the effects of drugs to enhance sexual pleasure as a primary reason for continued drug use. Methamphetamine (Meth) is commonly used in this context. Similarly, male rats that self-administered Meth immediately followed by sexual behavior display enhanced drug-seeking behavior, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Anterior cingulate cortex (ACC) can be activated by pleasurable events. [65][66][67][68] Interestingly, one brain imaging work reported that the ACC is significantly deactivated after active or passive scratching of itch. 62 Regression analyses of brain activity versus pleasurability ratings showed that areas including the ACC deactivated while actively scratching an itch coincided with areas significantly correlated with pleasurability.…”
Section: Anterior Cingulate Cortex Modulates Pleasure After Scratchingmentioning
confidence: 99%
“…Anterior cingulate cortex (ACC) can be activated by pleasurable events. [65][66][67][68] Interestingly, one brain imaging work reported that the ACC is significantly deactivated after active or passive scratching of itch. 62 Regression analyses of brain activity versus pleasurability ratings showed that areas including the ACC deactivated while actively scratching an itch coincided with areas significantly correlated with pleasurability.…”
Section: Anterior Cingulate Cortex Modulates Pleasure After Scratchingmentioning
confidence: 99%
“…• Concurrent Meth SA 1 mating induced higher extinction responding and Meth priming-induced reinstatement than nonconcurrent Meth SA 1 mating (see text for description of the two conditions) • Sex-induced reinstatement was only observed when mating in the concurrent group had occurred in the Meth SA context but not in a nondrug context 15 Kuiper et al, 2020 Meth Male SD rats…”
Section: Effect Of Maternal Behavior On Cocaine Cppmentioning
confidence: 99%
“…Brain mechanisms. Kuiper et al (2020), using immunohistochemistry and chemogenetic approaches, showed that noncontingent methamphetamine injections and mating coactivated CaMKII-expressing neurons in anterior insular cortex (ACC). Additionally, inhibition of CaMKII-expressing ACC neurons decreased the potentiation effect of concurrent methamphetamine self-administration 1 mating on drug cue-and drug priming-induced reinstatement but not extinction responding.…”
Section: Effects Of Sexual Interaction On Methamphetamine Self-admini...mentioning
confidence: 99%